Are rural residents missing out on teaching? A comparison of teaching opportunities for urban and rural family medicine residents at the University of Manitoba - Aaron Jattan (Canadian Medical Education Journal, 2018)
Background: The scholar competency of the CanMEDS-FM framework requires residents to develop teaching skills, and with the number of rural residency positions tripling over the last decade, it is essential for residency programs to provide rural residents with teaching opportunities. The purpose of this study was to investigate the differences in teaching opportunities offered to urban and rural family medicine residents at the University of Manitoba. Methods: The 117 urban and rural family medicine residents were surveyed to quantify their interactions with medical students. Specific respondents were interviewed to provide context to the survey. Results: On family medicine, only 20% of rural residents reported frequent opportunities to informally teach, compared to 57% of urban residents. Similarly, 86% of urban residents reported organized teaching opportunities compared to only 5% of rural residents. Residents placed high value in receiving additional teaching opportunities. Conclusion: This study suggests that there are fewer teaching opportunities for rural family medicine residents compared to urban residents at the University of Manitoba. Given the small sample size, a larger study could determine whether this trend exists across the country. It will be incumbent on residency programs to ensure rural residents have the opportunities to become competent educators.